THE MIDDLE PRECLASSIC FIGURINES FROM CAHAL PECH, BELIZE VALLEY. Issue 2 (2019) - Peniche May, Nancy; DeLance, Lisa; Awe, Jaime J.
Abstract: Ceramic figurines are ubiquitous throughout the archaeological record of Mesoamerica. These small, handheld objects continue to fascinate archaeologists, and their role in the daily lives of the people who created and used them remains a point of debate in some academic circles. The figurines have been interpreted variously as children's toys, fertility fetish tools, and ritual objects. At the site of Cahal Pech, located in the Belize Valley of west-central Belize, a large assemblage of figurines has been recovered from construction fill dating to the Cunil (1200–900b.c. ) and Kanluk ceramic phases (900–350b.c. ) of the Preclassic period. In this article, we analyzed the temporal and spatial distribution of these objects in the settlement and conclude that these objects were used in a variety of ritual events. Although they mainly served as venues for invoking ancestors in domestic rituals, their discovery in public spaces suggests diverse social uses. Most importantly, their limited presence in residential and public spaces outside the Plaza B section of the site core during the late facet of the Kanluk phase may indicate that certain rituals were not performed by the entire community.